Pengaruh Kualitas Sumber Daya Manusia Terhadap Pelaksanaan Sistem Pengendalian Inter Pada PT. Avia Avian - Rika Liftiana; Nur Maulana Iqbal (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2024)
This study aims to analyze the influence of human resource (HR) quality on the implementation of internal control systems at PT. Avia Avian. The background of this study is based on the importance of the role of quality HR in supporting the effectiveness of the implementation of internal control systems in companies. An effective internal control system is essential to maintain integrity, efficiency, and compliance with applicable regulations. The purpose of this study is to identify and analyze how HR quality can affect the implementation of internal control systems in companies. The method used in this study is a quantitative approach using a survey of employees in various departments of PT. Avia Avian. The data obtained were analyzed using regression techniques to examine the relationship between HR quality variables and internal control systems. The findings of the study indicate that there is a significant influence between HR quality and the implementation of internal control systems, where the better the quality of HR, the more effective the implementation of internal control systems. The implication of this study is that companies need to pay attention to improving HR quality as a strategic step to strengthen the existing internal control system, which in turn can improve the company's performance and compliance with established standards.Additionally, this research shows that continuous training and employee competency development can strengthen HR quality, which in turn contributes to the effectiveness of the internal control system. Companies that invest in improving HR quality will not only benefit in terms of compliance with regulations but also in enhancing operational efficiency and risk management. Therefore, it is crucial for the management of PT. Avia Avian to continue focusing on HR development to ensure the smooth implementation of internal control systems in accordance with applicable standards. This research contributes to the literature on risk management and internal control by highlighting the crucial role of HR quality in the success of internal control systems.